2017
DOI: 10.25301/jpda.262.79
|View full text |Cite
|
Sign up to set email alerts
|

BDS Curriculum: Neglected Sibling

Abstract: Third year BDS Ibad-ur-Rehman 3 First year MBBS ABSTRACT:The medical educationists are emphasizing on the implementation of skills based curriculum which covers the oral health in a broader and global scale. Keeping in mind these things this study was conducted to know opinion of medical students regarding modern educational reforms and the present curriculum taught in their medical colleges. Methodology: This survey was done in medical colleges with four year program in dentistry in Rawalpindi and Islamabad. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Research [13] have concluded that motivation and performance of student for a particular subject improves if it is delivered in accordance to their learning styles; a study done concluded that for effective delivery of anatomy concepts the instructors should be aware of diverse learning styles and how to manage them [14] . National research in undergrad dental colleges found that teaching strategies like problem-based learning (PBL) linking Basic and Clinical sciences with community health can bring significant change in educational approach of dental students [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Research [13] have concluded that motivation and performance of student for a particular subject improves if it is delivered in accordance to their learning styles; a study done concluded that for effective delivery of anatomy concepts the instructors should be aware of diverse learning styles and how to manage them [14] . National research in undergrad dental colleges found that teaching strategies like problem-based learning (PBL) linking Basic and Clinical sciences with community health can bring significant change in educational approach of dental students [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature in Pakistan has highlighted the lack of growth in professionalism in dentistry. This is due to lack of effective professionalism curriculum despite presence of subjects to address this need and justifying the need for a formal curriculum on professionalism (5,17) . It is necessary to assess this competency at an undergraduate level in order for graduates to achieve clinical excellence.…”
Section: Discussionmentioning
confidence: 99%
“…It can be presumed that students entering dental schools already possess some preconcept towards professionalism gained from previous experiences. The current dental curriculum is traditional and is not spiraled, other methods that bring change in students' behavior are not encouraged (4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…Individual interviews were conducted, and concurrent verbal probing technique was employed during the process. 4 The criteria of cognitive validity included: comprehension of the concept, coherent elaboration, and congruent answer. The final questionnaire was given to 27 faculty members to establish its reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies also suggested the need for modern teaching-learning methodologies as part of IC to produce competent HCPs in Pakistan. 4 Following the guidelines of PM&DC as well as the recommendations found in the literature, UCMD, UOL implemented IC.…”
Section: Introductionmentioning
confidence: 99%